PENERAPAN METODE OUTDOOR LEARNING UNTUK MENINGKATKAN KREATIVITAS SISWA PADA PEMBELAJARAN IPAS DI KELAS V MI FITYATUL ULUM PELEPOK GERUNG TAHUN PELAJARAN 2025/2026 - Hidayati, Devi; Taufik, Amalia; Hamzan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the low level of students’ creativity in IPAS learning in Grade V at MI Fityatul Ulum Pelepok Gerung, as indicated by limited participation in asking questions, lack of confidence in expressing ideas, and minimal idea generation during tasks. This study aimed to improve students’ creativity through the implementation of the outdoor learning method. The research employed Classroom Action Research (CAR) conducted in two cycles, consisting of planning, action, observation, and reflection stages. The subjects were 16 fifth-grade students. Data were collected through observations of teacher and student activities and a creativity questionnaire. The data were analyzed descriptively using qualitative and quantitative approaches. The results showed a consistent improvement in each cycle. In Cycle I, teacher activity reached 65.83% (good), student activity 62.5% (fair), and students’ creativity averaged 65.94% (good). In Cycle II, teacher activity increased to 82.5% (very good), and student activity to 85% (very good), while students’ creativity improved to an average of 88.75% (very good). These findings indicate that the outdoor learning method effectively enhances student participation, confidence, and ability to generate diverse ideas. Therefore, the implementation of outdoor learning can improve students’ creativity in IPAS learning.